Five power defense arrangement at forty - Storey, Ian; Emmers, Ralf; Daljit Singh (Institute of Southest Asian Studies, 2011)
Established in 1971 by Singapore, Malaysia, Britain, Australia and New Zealand, the Five Power Defence Arrangements (FPDA) has proved to be one of Asia's most enduring military pacts. Since its foundation, the FPDA has functioned as an important confidence building measure between its two Southeast Asian members, and has facilitated interoperability, professionalization and cooperation among the armed forces of the five countries. Crucially, its inherent flexibility and adaptability has enabled it to respond effectively to changes in the geopolitical environment as well as the emergence of new security threats. Now in its fortieth year, the FPDA remains a valuable component of Asia's security architecture in a time of change and uncertainty